Health Value Added of Healthcare Entities - Wiktor Ejsmont; Janusz Łyko (Ekonometria)
The paper deals with an evaluation of the quality of services provided by healthcare organizations. First, an index representing a patient's health condition is described, then its changes before and after being treated by a given entity are employed as a criterion to assess the operations of this entity. The index of a patient's health condition is based on the theory of survival analysis, while a model of random effects is used to determine the quality of services based on health value added.(original abstract)